PADAMU IVA “Peningkatan Kesadaran Deteksi Dini Kanker Serviks Melalui Edukasi Dan Pemeriksaan IVA” - Noormah Juwita; Lisa Ardiningtyas; Suci Pebrianti; Kristina Tumba Tandung (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Cervical cancer is one of the reproductive diseases in women with a high mortality rate. The occurrence of cervical cancer can be detected through the VIA method, which is a screening technique that involves applying a 3–5% acetic acid solution to the cervix and observing any color changes. This aims to identify cancerous or precancerous cells that are undergoing dysplasia. The purpose of this activity is to increase women's knowledge about early detection of cervical cancer through VIA screening. Methods: Health education was conducted through direct educational sessions using illustrated leaflet media, accompanied by pretest and posttest assessments to measure participants' level of knowledge before and after the intervention. Results: 70% of participants showed an improvement in their level of knowledge regarding cervical cancer and the IVA Test. This can be seen in both pretest and posttest activities conducted before and after both education.